Kidney transplant surgical director training: Urologists represent a functional alternative to general surgeons. Issue 8 (22nd June 2021) - Chiodo Ortiz, A.; Choubey, Ankur P.; Pai, K.; Khan, S.; Mishra, A.; Bullock, B.; Sureddi, S.; James, R.; Siddique, A.B.; Koizumi, N.; Ortiz, J.
Abstract: Introduction: Kidney transplant (KT) directors are general surgeons or urologists. All KT centers must meet established performance standards. However, it has not been established if general surgery and urology led programs have disparate outcomes. Methods: Transplant outcomes and donor‐recipient characteristics by director training were investigated. Organ Procurement and Transplantation Network (OPTN) directory, program websites were analyzed for surgical director demographics. Scientific Registry of Transplant Recipients (SRTR) 1‐year kidney survival and deceased donor (DD) wait‐time rankings were evaluated. A retrospective analysis of 142 157 KT recipients from 2010 to 2019 was performed using the United Network for Organ Sharing (UNOS) database. Results: One hunderd and seventy three (90.6%) KT programs were led by general surgeons. There were no significant differences in gender, ethnicity, region, credentials, or fellowship completion. Recipients undergoing KT with urology led programs were older ( P = .002) and had longer wait‐times ( P < .001). These centers used higher KDPI (.47 vs. .45, P < .001) and higher HLA mismatch (3.92 vs. 3.89, P = .02) kidneys. Urology led centers utilized living donors less frequently (32.1% vs. 35.8%, P < .001) and had longer CIT (15.44 vs. 12.21, P < .001). Both had similar SRTR ranking of 1‐year survival and DD wait‐time. Conclusion: Most directors were general surgeon. Patient outcomes did not differ by transplant director training. Urologists represent a viable option for KT leadership and recruitment should be encouraged.